Comparative Investigation of Intrusion Mechanics of Burstone Segmental Arc Technique and Ricketts Bioprogressive Treatment Technique in the Treatment of Adult Deep Sealed Closure Cases - Clinical Pilot Study - Banu Çakırer; Aslı Ender Telli (Galenos Yayinevi, 2001)
The purpose of this study was to compare the skeletodental changes and the efficacy of overbite correction achieved by Ricketts Bioprogressive Therapy and Burstone Segmented Arch Technique. The sample comprised 15 patients who have passed the peak pubertal growth period and who had brachifacial or mesofacial growth patterns with at least 3 mm overbite. Eight patients were treated with upper and lower utility arches and seven patients were treated with upper and lower base-arches. Lateral cephalograms, taken before treatment (Tl) and immediately after the overbite correction was achieved (T2), were evaluated. Statistical analysis was performed on the collected data. Both techniques produced a highly significant overbite reduction. Minimal increases in facial gnomon, oral gnomon and horizontal plane-mandibular plane angle due to treatment, did not effect anterior facial height significantly in neither of the groups. Both groups showed significant upper incisor intrusion however it was more in the Burstone group than in the Ricketts group. Intrusion of lower incisors in the Burstone group was significantly different from the minimal vertical position changes these teeth displayed in the Ricketts group. Lower incisor proclination was not significant in neither of the groups. However, the increase in the pro-clination of upper incisors in the Ricketts group was significantly different from the minimal increase in the Burstone group.